Finding Room in Beirut: Places of the Everyday - Lévesque, Carole (Earth, Milky Way punctum books, 2019)
Finding Room in Beirut: Places of the Everyday demonstrates why it is worth our while to explore the value and contemporary meaning of urban areas about to undergo complete renewal. Branching off from discourses surrounding the terrain vague, the book argues that large populated urban areas meet the criteria of the vague and constitute a particular perspective from which to build a critical stance in regards to the contemporary city. But unlike a terrain vague, a vague urbain inhabited areas where property ownership is usually obscure and informal behaviours a daily affair possesses real communities and offers an alternative understanding on how a city can be practiced and how lessons should be learned before its complete transformation. Stemming from a photographic and architectural documentation of Bachoura, a central area of Beirut, Lebanon, the book shows how the vague urbain allows for different ways of inhabiting, ways that are as or perhaps even more real and anchored in the imagination of the city as those proposed by standardising developments. Building on the intricacies of found situations, improvised uses and local narratives, it is an exploration as to how the meeting of a marvellous realism with l intrigue, the vague urbain, and temporary architecture can provide opportunities for the emergence of hidden narratives.
English
Keywords: Urban & municipal planning; urban design; Beirut; architecture; Lebanon; political geography; terrain vague; cultural studies